Cyber balkanisation : distraction to the essence of 1Malaysia / Rahmat Ghazali - Ghazali, Rahmat (Universiti Teknologi MARA, Shah Alam, 2010)
The concept of cyber balkanisation was initially coined by Cass Sunstein (2001) in Republic.com. It theorises the Internet phenomenon that caused users to be segregated and isolated and to gradually form their own like-minded colonies. Through such character, they hold the tendencies of being hostiled to others who do not agree with them. One of the causal factors highlighted in Sunstein’s theory is the Internet technology that allows users to customise, filter and select their needs and wants. Such Internet customisation, filteration and selection are easily prospered among multiethnic Malaysians who had been naturally segregated by their culture, religious belief, education and mother tongues. This social character is further supported by the freedom conferred to the Internet through the Communication and Multimedia Act 1998 that places the new media on a different track to that of the traditional one. However, there are paradoxes to such stance when cyber freedom could also be abused and exploited, thus challenging the national envision of 1Malaysia or otherwise ‘national integration’, particularly in creating an empathetic, interethnic relation among the multiethnic groups. The ideal Malaysian vision is therefore distracted because the mainstream thought of harmonious interethnic relation as envisioned by the 1Malaysia concept is jeopardised through social fragmentation and polarisation via cyber activism. This article shows that there are tendencies of cyber balkanisation among Malaysian Internet users even though the social reality did not suggest any incident of social hostility linked to the Internet.